Features of the Atrophic Corpus Mucosa in Three Cases of Autoimmune Gastritis Revealed by Magnifying Endoscopy - Kazuyoshi Yagi; Atsuo Nakamura; Atsuo Sekine; David Graham (Case Reports in Medicine)
Atrophic gastritis, whether caused by Helicobacter pylori infection or as a result of an autoimmune process, is associated with corpus atrophy. However, whereas atrophic gastritis caused by H. pylori involves the antrum, the antrum is spared in autoimmune gastritis. Here, we report the use of magnifying endoscopy to identify and distinguish atrophic gastritis caused by H. pylori from autoimmune gastritis. The mucosal pattern in autoimmune gastritis is that of closely arranged small round and oval pits, thus differing from the pattern seen in atrophic mucosa due to H. pylori infection. We speculate that this reflects differences in inflammation between the two types of gastritis. In autoimmune gastritis the inflammation is directed primarily against gastric glands, whereas in H. pylori infection the inflammation is directed against the bacteria on or near the surface and the damage initially affects the surface epithelium. During repair, the normal regular round pits are destroyed, whereas they remain largely intact in mucosa with autoimmune-associated atrophy. Confirmation of the features of autoimmune gastritis revealed by magnifying endoscopy would not only make the endoscopic diagnosis of autoimmune gastritis more accurate, but also help to elucidate changes in the surface epithelial structure of gastritis due to various causes.